Effect of vibration on the efficiency of ultrafiltration - Szerencsés, Szabolcs Gyula; Beszédes, Sándor; László, Zsuzsanna; Veréb, Gábor; Szegedi, Balázs; Horváth, Zsuzsanna Hovorkáné; Hodúr, Cecilia; Rákhely, Gábor; Kertész, Szabolcs (Analecta Technica Szegedinensia, 2021)
Nowadays, several environmental challenges are present to cope with. One with outstanding importance is the protection of our water supplies, therefore examination of wastewater treatment technology is a priority, especially in the European Union. In this work, the effect of membrane module vibration amplitude on the efficiency of ultrafiltration (UF) was investigated in a vibratory shear enhanced membrane filtration system. Based on the results of model dairy effluent UF and statistical analysis, the maximum vibration level available resulted in the most efficient filtration process, due to the most significant reduction of membrane fouling. From our results it was observed that the permeate fluxes more than doubled, specific energy demand was roughly halved, with almost identical retentions for organic matter, and total filtration resistance was reduced to less than half. Results also showed that setting the optimal operating parameters, an advantageous, efficiency focused, and sustainable wastewater treatment technology can be established.